Optimizing remote ischemic conditioning (RIC) of cutaneous microcirculation in humans: Number of cycles and duration of acute effects. Issue 4 (April 2021) - Sogorski, A.; Spindler, S.; Wallner, C.; Dadras, M.; Wagner, J.M.; Behr, B.; Lehnhardt, M.; Kolbenschlag, J.
Summary: Objective: Non-invasive Remote Ischemic Conditioning (RIC) offers an approach to reduce tissue damage in various organs/tissues. Besides attenuation of Ischemia-Reperfusion injury (I/R), beneficial effects on cutaneous microcirculation of free microsurgical flaps have been reported. Given the recency of this technique, there are considerable gaps in the current understanding of its mechanism of action. As a result, clinical transfer of RIC is prolongated in several fields. We aimed to optimize the RIC protocol by examination of different RIC-cycle numbers and its effect on changes of cutaneous microcirculation and duration. Methods: 80 subjects were divided into groups (1, 3, 5, 7 RIC cycles). RIC was applied via an inflatable tourniquet. Cutaneous microcirculation was continuously assessed at the contralateral anterior lateral thigh utilizing a ©O2C-device continuously. Results: RIC caused significant and sustained changes in microcirculation. Four hours after completion of RIC, a maximum increase of +80.8% (CI 1.395–2.221) in blood flow and +23.5% (CI 1.098–1.372) in tissue oxygen saturation was measured (three-cycle group). A higher number of applied cycles was accompanied with significant higher mean pain. Conclusion: Acute improvement of cutaneous microcirculation due to RIC lasted for at least 4 h after completion of the RIC-protocol. Dose-dependent effects of RIC are likely. With regard to the increase in pain, we recommend a RIC protocol of 3 cycles for future clinical application.